Bosques en Bolivia: Una estimación espacial de los costos de la deforestación - Alejandra Gonzalez Rocabado (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2019)
– Deforestation in Bolivia has increased considerably during the last few decades, which causes carbon dioxide emissions, biodiversity loss, changes to the hydrologic cycle, among others. This study pretends to estimate the impacts and costs of that deforestation. Since each variablehas its own complexity, the use of different methodologies is necessary. The first model used is a carbon bookkeeping model and the carbon price. The second is the BIOM model which is based on the extrapolation of species, and the use of the elasticity between consumption and absolute species richness for the quantification of costs. Finally, a spatial econometric model and a water scarcity index are used for the estimation of the costs of variation in the hydrologic cycle. The results are presented at three levels; a national level, department level and municipal level for two time periods; 1990-2000 and 2000-2010. In addition, based on the results, conclusion and recommendations are formulated about deforestation in Bolivia. This study calculates that the cost of deforestation in Bolivia exceeds 10% of GDP.
Keywords: Q23; Q24; Q25; Q57; Q31; Q32; 330; Deforestation; forest; carbon emissions; biodiversity loss; hydrologic cycle variation